Synthesis, Crystal Growth, and Computational Investigation of New Tetrahydroisoquinoline Derivatives Potent against Molecule Nitric Oxide Synthases - Youness El Bakri; Shaaban K. Mohamed; Atazaz Ahsin; Subramani Karthikeyan; Suzan Abuelhassan; Abdu E. Abdel-Rahman; Islam S. Marae; Etify A. Bakhite; Joel T. Mague; Rashad Al-Salahi (Crystals, 2023)
In the present work, we describe the synthesis of new tetrahydroisoquinoline derivatives and the crystal structures of two of them. Density functional theory (DFT) investigations at the B3LYP/6-31+G(d,p) level provided their structural reactivity and nonlinear optical properties. The low HOMO-LUMO gaps (EH-L) suggest a soft nature and higher reactivity, while calculated global reactivity descriptors provide assessments of their reactivity and electronic stability. The calculated natural bonding molecular orbital (NBO) charges show excellent charge separation (charge transfer) and identify the donor and acceptor parts of the molecules. Density of states (DOS) analyses show the newly generated energy states and reduced band gaps, which impart higher conductive properties. For surface reactivity, 3D MESP surfaces are plotted and show electron-rich sites near the nitrogen atoms of the tetrahydroisoquinoline rings. Nonlinear optical (NLO) properties of the crystals are predicted from calculated polarizability (αo) and hyperpolarizability (βo) values. For IVb, the αo and βo values are 415.53 and 1003.44 au. The remarkable value (1003.44 au) of the hyperpolarizability (βo) shows IVb has excellent NLO properties. Structural activity relationship analysis suggests that nitric oxide synthases are better targets for both compounds, and they were further subjected to molecular docking simulations to understand the binding efficiency. In addition, ADMET analyses were carried out to understand the potential activity of the molecules as drug candidates.